Imatinib enchances the sensitivity of gastrointestinal stromal tumors to topoisomerase II inhibitors - S. V. Boichuk; A. R. Galembikova; B. R. Ramazanov; A. Duensing (Успехи молекулярной онкологии, 2015)
Objective: to study the sensitivity of gastrointestinal stromal tumors (GISTs) to the topoisomerases type II inhibitors and ability of imatinib to enhance GISTs sensitivity to the chemotherapeutic drugs indicated above.Subjects and Methods. We studied the sensitivity of gastrointestinal stromal tumors (GISTs) to the topoisomerases II inhibitors and ability of imatinib to enhance GISTs sensitivity to these chemotherapeutic agents. The expression of DNA damage and repair (DDR) markers was examined by western-blotting. Cleaved forms of poly (ADP-rybose) polymerase and caspase-3 were served as an apoptotic markers measured by western blotting. Amount of apoptotic cells was counted by flow cytometry analysis by using a propidium iodide DNA staining procedure and counting the numbers of hypodiploid cells.Results. We observed the sensitivity of GISTs to topoisomerase II inhibitors – doxorubicine and etoposide inducing DNA double-strand breaks and apoptotic cell death. Imatinib enhances GISTs sensitivity to topoisomerase II inhibitors. This might be due to reduced ability of GISTs to repair DNA damage by homologous recombination. Imatinib-induced reduction of Rad51 recombinase might be due to increased proteasome-dependent degradation.Conclusion. GIST cells are sensitive to topoisomerase II inhibitors (etoposide and doxorubicin) in vitro. Imatinib enhances GISTs sensitivity to the chemotherapeutic agents indicated above.